Variations in ischemic heart disease burden by age, country, and income: the Global Burden of Diseases, Injuries, and Risk Factors 2010 study. - Moran,AE; Tzong,KY; Forouzanfar,MH; Rothy,GA; Mensah,GA; Ezzati,M; Murray,CJL; Naghavi,M (Glob Heart, 2014)
BACKGROUND: Ischemic heart disease (IHD) was the leading cause of disease burden worldwide in 2010. The majority of IHD burden affected middle-income regions. We hypothesized IHD burden may vary among countries, even within the same broad geographic region. METHODS: Disability-adjusted life years (DALYs) due to IHD were estimated at the region level for 7 “super-regions,” 21 regions, and 187 countries using geographically nested models for IHD mortality and prevalent nonfatal IHD (nonfatal acute myocardial infarction, angina pectoris, or ischemic heart failure). Acute myocardial infarction, angina, and heart failure disability weights were applied to prevalent cases. Absolute numbers of DALYs and age-standardized DALYs per 100,000 persons were estimated for each region and country in 1990 and 2010. IHD burden for world regions was analyzed by country, income, and age. RESULTS: About two-thirds of 2010 IHD DALYs affected middle-income countries. In the North Africa/Middle East and South Asia regions, which have high IHD burden, more than 29% of men and 24% of women struck by IHD were <50 years old. Age-standardized IHD DALYs decreased in most countries between 1990 and 2010, but increased in a number of countries in the Eastern Europe/Central Asia region (>1,000 per 100,000 increase) and South Asia region (>175 per 100,000). Age-standardized DALYs varied by up to 8-fold among countries, by about 9,000 per 100,000 among middle-income countries, about 7,400 among low-income countries, and about 4,300 among high-income countries. CONCLUSIONS: The majority of IHD burden in 2010 affected middle-income regions, where younger adults were more likely to develop IHD in regions such as South Asia and North Africa/Middle East. However, IHD burden varied substantially by country within regions, especially among middle-income countries. A global or regional approach to IHD prevention will not be sufficient; research and policy should focus on the highest burd